AC-ECM for SPICEcore - Fudge, T. J.; Waddington, Edwin (IEDA: US Antarctic Program Data Center, 2019)
Abstract: These are AC-ECM data used to identify volcanic events in SPICEcore. The data have been normalized to get a consistent baseline for data collected from three different processing seasons.